PENGARUH MEDIA MARIONETTES TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Rafika Yanti; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on observationsin the field it can be seen that listening ability of children aged 5-6 years has not developed optimally. So the need to use a media marionettes. The aim of this research is to know the effect media marionettes on the ability to listening children’s age 5-6 years. The research is conducted in TK Negeri Pembina 1 Pekanbaru from April to Mei 2017. This is pretest and posttest group design an experimental research with 30 children as samples. Type of instrument used in this study is the observation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are the shaping technique is influence on listening ability children ages 5-6 years in TK Negeri Pembina 1 pekanbaru. Retrieved t count at 8,613 with sig 0000, because sig <0.05 then we can conclude that there are influence on the ability to listening is significant between class with media marionettes and without media marionettes. Hypothesis testing can be seen at tcount= 8,613> t table = 2,048 it has been suggested that there is a significant influence in results between the control class and experiment class. The media marionettes had a significant effect towards children’s age 5-6 years old listening ability, at 63,70%. This is known from the different results listening ability on control class and expriment class with given media marionettes treatment.Keywords: Listening Ability, Media Marionettes